1987
DOI: 10.1159/000156287
|View full text |Cite
|
Sign up to set email alerts
|

Baboon Diet: A Five-Year Study of Stability and Variability in the Plant Feeding and Habitat of the Yellow Baboons (Papio cynocephalus) of Mikumi National Park, Tanzania

Abstract: The habitat and plant feeding of 64 well-habituated, individually identified adult male and female yellow baboons was studied for 5 years at Mikumi National Park, Tanzania. Variation across the years showed that a study of only one or two years would have been incomplete and misleading. The list of baboon food species obtained from Mikumi is considerably larger and more diverse than any previously reported. One to six plant parts were eaten from each of more than 180 species. The 25 most common tree genera all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 16 publications
6
82
0
Order By: Relevance
“…For the most part, baboons within a given region appear to develop a fixed or staple diet, most evinced in the smaller degree of variation between hair and tooth samples than intraindividually (Codron et al 2006). In field studies of baboons in southern and East African environments, Norton et al (1987) and Byrne et al (1993) made similar observations, in that staple food items of populations remain fairly consistent through time with only perimeter items varying in substantial ways The implication is that australopiths were either even more generalist than baboons, or that the variation in early hominin enamel ÎŽ 13 C likely represents individuals from different populations isolated in space or time. Fecal samples collected at monthly intervals portray a similarly high degree of variation as exists across multiple hominin enamel specimens, but the 2 lines of evidence are not strictly comparable because of the short-term nature of feces as dietary indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the most part, baboons within a given region appear to develop a fixed or staple diet, most evinced in the smaller degree of variation between hair and tooth samples than intraindividually (Codron et al 2006). In field studies of baboons in southern and East African environments, Norton et al (1987) and Byrne et al (1993) made similar observations, in that staple food items of populations remain fairly consistent through time with only perimeter items varying in substantial ways The implication is that australopiths were either even more generalist than baboons, or that the variation in early hominin enamel ÎŽ 13 C likely represents individuals from different populations isolated in space or time. Fecal samples collected at monthly intervals portray a similarly high degree of variation as exists across multiple hominin enamel specimens, but the 2 lines of evidence are not strictly comparable because of the short-term nature of feces as dietary indicators.…”
Section: Discussionmentioning
confidence: 99%
“…In field studies, Altman (1998), Barton et al (1993), Byrne et al (1993), DeVore and Hall (1965), Dunbar and Dunbar (1974), Norton et al (1987), Whiten et al (1991), and others revealed that baboon diets, excluding the primarily stenotopic graminivore Theropithecus gelada, vary in extreme ways. Stable isotope ecology is one tool that enables researchers to characterize and to quantify at least some aspects of diet in these and other generalist feeders in easily understandable terms.…”
Section: Introductionmentioning
confidence: 99%
“…Our investigation provides an important extension of previous research on optimal group size, which has focused predominantly on fission-fusion species, in which group size changes frequently in response to immediate conditions (25). Within a baboon population, the home ranges of social groups overlap extensively, and foraging resources [primarily plant foods (26,27)], are often located within regions of home range overlap (28). However, despite this home range overlap, groups rarely come in close proximity with one another, indicating that baboon groups temporally partition the landscape, using the same resources but at different times (29).…”
Section: Significancementioning
confidence: 90%
“…Orangutans are intermediate in their diets. Finally, geladas are specialized grass eaters, whereas yellow baboons have a more catholic diet including fruits, leaves and animal prey (see Post 1982;Norton et al 1987;Dunbar 1988;Altmann 1998;Pochron 2000;Bentley-Condit 2009). …”
Section: Methodsmentioning
confidence: 99%